A notation for Goal Driven Interfaces Specification. - Carrillo-León, Antonio Luis; Falgueras-Cano, Juan; Guevara-Plaza, Antonio (Springer Nature, 2006)
Although direct manipulation with WIMP (Windows, Icons, Menus and Pointer) elements is currently the most extended user interface paradigm in use, there are still many users that need a training and learning period, manuals and/or expert support to become efficient users. We present here a new and alternative style of interaction: Goal Driven Interaction (GDI). GDI was meant to become the interaction style of choice for applications where the main priority is ease of use and minimal learning time for a user to interact with the program, even if sacrificing speed in task achievement, the ability of running parallel tasks and other advantages of WIMP interfaces. GDI’s main philosophy is to guide the user in a hierarchical and progressive way through the whole interaction process, not only as far as the tasks and goals approach are concerned, but also about the sequence of steps to follow or the choices that can be made at any given moment to achieve those goals. Two aspects are considered fundamental for the success of GDI and the interfaces supporting them. The first of them is the fact that their specification and design process can be carried out based on main interface engineering techniques and methodologies, as those based on tasks hierarchical analysis, whose importance, usefulness and other advantages are widely recognized. Nevertheless, even the most adequate, Kieras’s notation, NGOMSL, needs to be adapted and extended, and that constitutes the main aim of this paper.
Política de acceso abierto tomada de: https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Interfaces de usuario; User interfaces specification; Notation; Guided interfaces